2013
DOI: 10.5114/pdia.2013.37031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impact of selected socio-demographic factors on quality of life of asthma patients

Abstract: AimTo evaluate the influence of selected socio-demographic factors on quality of life of patients with different degrees of asthma severity.Material and methodsThe study was conducted in 2009–2010 in the Clinic of Allergology, Clinical Immunology and Internal Diseases in Dr J. Biziel University Hospital No. 2 in Bydgoszcz. Patients were divided into a tested group (126) and a control group (86). The criterion for the division was the degree of asthma control according to GINA 2006. The following tools were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
3
5
0
1
Order By: Relevance
“…Disability pensioners had a significantly lower QoL in this domain than professionally active respondents. Similar results were obtained by Szynkiewicz et al 13 in their study on the impact of sociodemographic factors on the HRQoL of patients with asthma. They confirmed that the professional status of respondents is a factor in their HRQoL.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Disability pensioners had a significantly lower QoL in this domain than professionally active respondents. Similar results were obtained by Szynkiewicz et al 13 in their study on the impact of sociodemographic factors on the HRQoL of patients with asthma. They confirmed that the professional status of respondents is a factor in their HRQoL.…”
Section: Discussionsupporting
confidence: 90%
“…Scores at 24–20 points indicate well-controlled asthma but not fully controlled asthma, while scores <20 points indicate uncontrolled asthma. 11 13 …”
Section: Methodsmentioning
confidence: 99%
“…33,34 This could be a major contributing factor on the impairment of their quality of life, as experienced by the unemployed patients. Similar results were expressed in an earlier study on the influence of sociodemographic factors on the HRQoL of asthma patients 6 and revealed that the professional activity of the patients is a contributing factor in their HRQoL. Another reason that can be associated with this, is the higher socioeconomic status achieved by individuals with higher qualifications.…”
Section: Discussionsupporting
confidence: 88%
“…Asthma patients often grumbles about the effects on their social, physical and psychological domains of life quality. 6 The modern treatment objective for asthma is to attain and preserve asthma control in a longterm perspectives including improvement of Health Related Quality of Life (HRQL) apart from managing clinical manifestations. 7 In regards to this, the HRQoL concept was initiated into clinical and medical practice in 1990s' .…”
Section: Introductionmentioning
confidence: 99%
“…Literatürde astımlı hastalarda cinsiyet ile yaşam kalitesi arasındaki ilişkiyi inceleyen çalışmaların bir kısmında cinsiyet faktörünün belirtilen skorlar üzerinde etkisinin olmadığı ve yaşam kalitesini etkilemediği ileri sürülmektedir (27). Literatürle uyumlu olarak kız ve erkeklerde zorlanılan faaliyetlerde ilk sırayı koşma almaktadır (28 …”
Section: Discussionunclassified